Ventilation and features of the lung environment dynamically alter modeled intrapulmonary aerosol exposure from inhaled electronic cigarettes - Liqiao Li; Haoxuan Chen; Yifang Zhu; Airi Harui; Michael D. Roth (Scientific Reports)
Abstract Electronic cigarettes (e-cigs) fundamentally differ from tobacco cigarettes in their generation of liquid-based aerosols. Investigating how e-cig aerosols behave when inhaled into the dynamic environment of the lung is important for understanding vaping-related exposure and toxicity. A ventilated artificial lung model was developed to replicate the ventilatory and environmental features of the human lung and study their impact on the characteristics of inhaled e-cig aerosols from simulated vaping scenarios. Compared to static conditions, normal breathing decreased peak particle number concentrations (PNCs) and area under the curve (AUC) by 40% and 70%, respectively, and increased particle decay rates fourfold. However, even with ventilation, intrapulmonary PNC levels exceeded 2 × 106 particles/mL in a 4-puff vaping session. Both respiratory rate and tidal volume modulated e-cig aerosol exposure in a manner inversely proportional to minute ventilation. The modeled lung environment (37 °C, 88% relative humidity) also significantly altered particle size distributions by facilitating aerosol transformations such as hygroscopic growth, which further impacted e-cig aerosol exposure and particle removal. This work highlights the dynamic nature of intrapulmonary exposures and underscores the need to account for lung physiology and environmental factors when assessing inhaled e-cig aerosols.